Mixed-method analysis of truck driver health knowledge using an online forum. (February 2018) - Versteeg, Katelyn; Amoli, Tina; Cao, Michael; Chin, Marissa; Bigelow, Philip; Yazdani, Amin
Highlights: We applied content analysis to posts of a trucker health forum to view health interest. Food, Nutrition, Chronic Illness and Medical Road Tests were the most popular themes. The content appeared to be mostly anecdotal with little scientific evidence. After 2009, the forum's traffic was found to decrease, suggesting decreased interest. Analysis suggest knowledge of disease types, but not prevention or treatments. Rasmussen's Risk Management Framework was used on a small section of posts. Posts showed little understanding towards the systems effect on trucker health. Abstract: Truck driving in North America is a high-risk occupation, with some of the highest rates of illness and injuries in comparison to other occupations (Sieber et al., 2014). This study aims to understand the knowledge that truck drivers have of health. Posts from The Truckers Report's Health Forum, an online forum for truck drivers, were coded into 1 of 11 determined codes to represent different aspects of health (The Truckers Report, 2016). Proxy measures such as Total Posts, views:post, replies:post, and views:reply were created to assess forum posts discussions. A total of 1760 forum posts were analyzed through qualitative coding and quantitative measures including rankings. Lastly, to determine how drivers' knowledge of the complex system affecting their health, 150 randomized forum posts were coded for Rasmussen's (1997) systems levels related to health risk. Overall, use of the Health Forum has decreased over time while other forums on the Truckers Report did not. This may represent a decrease in value or engagement towards health from truckers. Analysis suggested that truck drivers had awareness of many of the codes, with the exception of safety, but very little knowledge within the themes. Furthermore, truck drivers indicated very little knowledge on how societal systems affect the health of the individual, and instead placed all the responsibility and outcomes related to health on the individual. When working to improve health in truck drivers, companies and health care professionals should be aware of a knowledge gap within drivers regarding their understanding of health and disease prevention.